Pengaruh Service Quality Terhadap Customer Satisfaction Taman Cadika Pramuka Johor di Medan - Furqan; Yogi Putra (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
The purpose of this study was to examine the effect of service quality on visitor satisfaction at Taman Cadika Pramuka Johor Medan City. The sample used in this study were visitors who visited Taman Cadika Pramuka Johor Medan City. This research design uses quantitative research. The sample used in this study were the visitors who came to Taman Cadika Pramuka Johor Medan City Medan City as many as 100 visitors, selected based on the Non-Probability Sampling technique with the Convenience Sampling technique. Collecting data in the form of a questionnaire. Likert scale questionnaire used to see the effect of Service Quality on Visitor Satisfaction. Meanwhile, the data required consists of two variables: Service Quality as the independent variable and Visitor Satisfaction as the dependent variable. The data analysis used in this study consisted of simple linear regression analysis with SPSS 22.0 and Microsoft Excel computer program with 100 respondents.The results of this study conclude that the service quality variable has an influence on visitor satisfaction. As evidenced by the Probability Significance level score is Sig. = 0.000. From the results, it can be seen that the significance is smaller than 0.05 (Sig. <0.05) while the results of the coefficient of the influence of the X variable on the Y variable = 0.738 or 73.8% which means that the results show that Service Quality has an effect on Visitor Satisfaction at Cadika Park. Johor Scouts, Medan City, Medan City.